Android client for nagios in monitoring Linux server / Ahmad Nazmie Ahmad Murad, Mohd Shaiful Harris Halim and Mohd A’idil Juhata - Ahmad Murad, Ahmad Nazmie; Halim, Mohd Shaiful Harris; Juhata, Mohd A’idil (2013)
System administrator and network administrator are responsible for continuity of respective servers, even when they are out of the server area. While smartphones usage is not just a trend; people critically need it to enhance works. Therefore, this project or VNag, presents usage of Android smartphones to monitor servers as a solution to the problem. Nagios is the most popular application for monitoring among those that exist on the market. Data derived from Nagios cgi-bin file, will be displayed on smartphone for remote viewing. Nagios parameter such as services, hosts, and information of server status, are fetched using HTTP GET. Upon having a request, server replies with HTTP RESPONSE and data is parsed by HTML parser JSOUP. The software is created using Eclipse Juno SDK, along with ADT and JSOUP. The work presents dynamic data fetch as different servers will have contrastive services. A test conducted reveals that the software is able to fetch data in less than 20 second. Although the traffic is heavy, the application is still working with higher delay. An incorrect URL, username and password will prohibit the user from continuing. The software enables system administrator and network administrator to remotely monitor their respective servers.